Социальный конфликт: проблема определения - Казаков, В. (Социология: теория, методы, маркетинг, 2004)
In the article, the definition of a conflict as a social phenomenon is discussed. The author analyses possible options of its logical construction, by kin and kind, in particular, with the help of the notions, such as contradiction, competition, collision. There are chosen the main invariant features of a conflict, some of them are specially stressed: active material and practical inter-influence, different social subjects, difficulties in satisfying needs, realization of interests and goals.